2002
DOI: 10.1093/jjco/hyf064
|View full text |Cite
|
Sign up to set email alerts
|

Is Daidzein Non-metabolizer a High Risk for Prostate Cancer? A Case-controlled Study of Serum Soybean Isoflavone Concentration

Abstract: The above findings revealed that equol itself or some unknown factor regulating the metabolism of daidzein is deeply involved in the biology of prostate cancer. Future studies are urgently needed to compare the incidence of daidzein metabolizers among various countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 19 publications
5
67
1
Order By: Relevance
“…Our present results revealed that the percentage of equol producers was lower (10-25%) in healthy Japanese men aged between 10 and 49 years than those in their fifties and that the proportions of equol producers in the sixties and seventies among the urologic disease-free and cancer-free control outpatients enrolled in our early study 18 were 54 and 59%, respectively, (Figure 1). Importantly, the percentage of equol producers was very low (10%) in the Japanese teenager as well as in the American healthy men (14%) in contrast to the Japanese and Korean healthy men (46 and 59%, respectively) in the present study in our previous case-control study.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Our present results revealed that the percentage of equol producers was lower (10-25%) in healthy Japanese men aged between 10 and 49 years than those in their fifties and that the proportions of equol producers in the sixties and seventies among the urologic disease-free and cancer-free control outpatients enrolled in our early study 18 were 54 and 59%, respectively, (Figure 1). Importantly, the percentage of equol producers was very low (10%) in the Japanese teenager as well as in the American healthy men (14%) in contrast to the Japanese and Korean healthy men (46 and 59%, respectively) in the present study in our previous case-control study.…”
Section: Discussionmentioning
confidence: 56%
“…[18][19][20] Those studies of the serum equol level revealed two types of men with different metabolic patterns of daidzein to equol; one group is equol producers and the other is equol non-producers whose serum equol was under the detection level (0.5 ng ml À1 ), and the proportion of equol producers among patients with prostate cancer was significantly lower than that among the agematched control group patients. 18 Moreover, the proportion of equol producers was significantly lower among patients with poorly differentiated adenocarcinoma than among those with well or moderately differentiated adenocarcinoma. However, the epidemiologic relationship between equol production ability and prostate cancer development has not been well elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies indicated that soy isoflavone consumption may protect against certain types of cancers, some hormone-related diseases (breast, prostate, and colon cancers etc.) and reduce bone loss, due to its estrogenic activities and other biological activities (Davies et al, 1999;Pool-Zobel et al, 2000;Akaza et al, 2002;Hikosaka et al, 2004;Hu and Knobf, 2004;Vastag, 2007;Ma et al, 2008;Taylor et al, 2009;Kang et al, 2010). Isoflavone biosynthesis is affected by several factors, and their concentration and profile mainly depend on genotype, environment, cultivation conditions and other conditions during seed maturation (Wang and Murphy, 1994;Caldwell et al, 2005;Chennupati et al, 2011;Vamerali et al, 2012).…”
mentioning
confidence: 99%